Penegakan Hukum Terhadap Pelaku Tindak Pidana Penganiayaan Anak dengan Menggunakan Restorative Justice - Fariza Raisa Rafania; Erna Dewi; Ahmad Irzal Fardiansyah; Maya Shafira; Sri Riski (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Violence against children remains a serious violation of human rights that continues to occur in various social environments, including religious-based educational institutions such as Islamic boarding schools, where children are in a highly vulnerable position both physically and psychologically. One case that drew public attention occurred at the Pesona Al-Qur’an Islamic Boarding School in Pesawaran Regency, which was resolved through a restorative justice approach without proceeding to court. This study aims to examine the mechanism of law enforcement against perpetrators of child abuse at the institution and to analyze the factors hindering the implementation of restorative justice in such cases. Using a normative-empirical research method, this study analyzes applicable laws and regulations supported by field data obtained through interviews, observations, and documentation. The results show that law enforcement was carried out through an investigation by the Pesawaran Resort Police, followed by the termination of prosecution by the Pesawaran District Prosecutor’s Office based on Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. Case resolution was conducted through mediation involving the perpetrator, the victim, and their families, facilitated by law enforcement officers, resulting in an agreement in the form of an apology and compensation to the victim. However, the implementation of restorative justice still faces several obstacles, including limited public understanding, concerns about the loss of deterrent effects, power imbalances between victims and perpetrators, potential pressure on victims to accept reconciliation, and weak supervision of post-mediation agreements; therefore, strengthening oversight, improving the understanding of law enforcement officers and the community, and optimizing the role of child protection institutions are essential to ensure that restorative justice truly prioritizes the best interests of the child and provides substantive justice.